Poetry for patrons : literary communication in the age of Domitian - Nauta, Ruurd R. (Mnemosyne, Supplements, 2002)
A study of the phenomenon of literary patronage, both non-imperial and imperial, during the reign of the Roman emperor Domitian (81-96 A.D.). This work centres on the Epigrams of Martial and the Silvae of Statius. The book deals not only with the relationships between poets and patrons, but also with the audiences and the functions of patron-oriented poetry. It includes discussions of such topics as \'patronage\' versus \'friendship\', the poetic \'I\', the role of poetry at symposia and festivals, dedication and publication, the influence of rhetoric on poetry, and the poetic representation of imperial power. The book should prove of interest not only to specialists in Roman poetry, but also to ancient historians and to students of literary patronage in other cultures. All Latin and Greek is translated.